Antoinet Schimmelpenninck. Chinese folk songs and folksingers: Shan’ge traditions in southern Jiangsu. Leiden: Chime Foundation, 1997. (incluye CD). - Sestili, Daniele; Lara, Gabriela (Estudios de Asia y África, 2002)
-